Temperature-dependency on adhesion force of ice made from surfactant–pure water mixture to copper surface. (July 2017) - Matsumoto, Koji; Minamiya, Kazuyuki; Sakamoto, Junki; Ueda, Jun; Ehara, Kohei; Yamanaka, Seiichi
Highlights: Shearing stress increased as surface temperature decreased. Increasing ice and Cu surface energies caused an increase in shearing stress. Drop in surface temperature caused an increase in both surface energies. Amount of surfactant adsorbed to the ice did not vary between −1 and −10 °C. Drop in shearing stress at the same temperature was caused by surfactant adsorption. Abstract: Since ice adhesion force to a cooling solid surface causes various problems, its reduction is important. Accordingly, after studying reduction methods from various viewpoints, the authors herein have focused attention on adsorption of the hydrophobic groups of surfactant molecules to a copper surface. And, the adhesion forces of ice made from the surfactant-mixtures at a fixed concentration to the copper surface at various temperatures were measured by the scanning probe microscopy. Simultaneously, adsorbed amounts of the surfactant molecules to the copper surface were measured by the quartz crystal microbalance system with varying surfactant mixture temperatures. Furthermore, the ice adhesion force depends on surface energy of ice, and the surface energy also depends on temperature. So, surface energies of ice were also measured with varying temperatures. And the influence of temperature-dependency of the surface energy on the surface temperature-dependency of the ice adhesion force was clarified considering the adsorbed amount of surfactant.